28. The safety of polypropylene mesh in nipple-sparing mastectomy and immediate implant-based breast reconstruction in early breast cancer patients - Tung, Bui Duc; Dung, Pham Xuan; Quang, Le Van (Tạp chí Nghiên cứu Y học, 2024)
The study aimed to determine the incidence and severity of postoperative complications in early breast cancer (BC) females undergoing immediate breast reconstruction (IBR) with implant and polypropylene mesh (PPM) after nipple-sparing mastectomy (NSM). This study is a retrospective, single-arm and single-institutional trial. The population selected was females with BC treated at Ho Chi Minh City Oncology Hospital from July 01, 2022, to Jan 31, 2024. The inclusion criteria included pathology as carcinoma of breast at preoperative stage as 0, I or II with tumor less than 3cm, and being treated with NSM followed by implant-based IBR with PPM. 28 patients met the inclusion criteria. Of two patients, the former had a late infection, whereas the latter suffered from nipple-areolar necrosis, accounting for 8% of all. Both patients were well managed with medical therapy. We did not find any statistical significance between the postoperative complications and relevant clinical and therapeutic characteristics. PPM enables the cavity to hold the implant, while still maintaining natural breast appearance. This is a safe surgical procedure to perform. PPM may be considered as an alternative for covering the lower anterior aspect of implant, especially in developing countries like Vietnam.